2009
DOI: 10.1111/j.1468-2370.2008.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

A review and synthesis of demand management, capacity management and performance in health‐care services

Abstract: Responses to demand uncertainty in the field of health-care services is a very timely research issue because of ongoing changes in demand patterns that are driven by demographics and recent changes in the delivery of these services. Despite its importance to researchers, the literature on demand management, capacity management and performance in health care has not been extensively reviewed. The present paper addresses this need by analyzing and synthesizing 463 articles published between 1986 and 2006. The ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 100 publications
(178 reference statements)
1
66
0
1
Order By: Relevance
“…However, costs of flexibility can be reduced by conceiving of flexibility in more creative ways (e.g., cross-training that has staff trained in multiple tasks versus adding staff). 17 Although cross-training may itself be cost-prohibitive where advanced training is required – e.g., additional degrees or schooling – it may be especially useful for tasks like performing electrocardiograms, patient re-evaluations, performing discharges, or taking vital signs.…”
Section: Flexibility In Other Industriesmentioning
confidence: 99%
“…However, costs of flexibility can be reduced by conceiving of flexibility in more creative ways (e.g., cross-training that has staff trained in multiple tasks versus adding staff). 17 Although cross-training may itself be cost-prohibitive where advanced training is required – e.g., additional degrees or schooling – it may be especially useful for tasks like performing electrocardiograms, patient re-evaluations, performing discharges, or taking vital signs.…”
Section: Flexibility In Other Industriesmentioning
confidence: 99%
“…Table 2 presents the remaning 16 reviews which present multiple types of applications and the classification of the applications of simulation studies, within those articles [7,8,12,14,16,18,20,22,25,27,28,33,34,36,37,39]. The numbers of simulation studies relating to the different application groups were identified and extracted from the sixteen reviews.…”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
“…Jack et al [12] Review of demand management, capacity management and performance in healthcare services…”
Section: -2007 34mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3.1 displays our search method. To identify the search terms as listed in Appendix 3.11.2 and to create the basic structure of the planning decision hierarchy for each care service, we consulted available literature reviews [49,59,61,74,84,89,99,166,182,183,224,228,229,271,282,287,289,304,336,351,363,368,393,399,404,410,413,451,452,479,491] and books [62,231,312,361,387,503]. Additional search terms were obtained from the index of Medical Subject Headings (MeSH) [362] and available synonyms.…”
Section: Literature Search Methodmentioning
confidence: 99%